Evaluation of Environmental Education Learning in the Era of the Merdeka Belajar Curriculum - Syaifudin, Syaifudin; Purwanto, Agung; Budiaman, Budiaman (IJBLE Scientific Publications Community Inc., 2024)
This article investigates the evaluation of Environmental Education learning in the era of the Independent Learning curriculum. The Independent Learning Curriculum, issued by the Ministry of Education and Culture of Indonesia, aims to provide freedom and autonomy to educational institutions in managing the learning process. With this policy, it is hoped that students can develop their competencies and character more optimally. This study analyzes how Environmental Education learning has been applied within the framework of Freedom of Learning, as well as evaluates the effectiveness and challenges faced. The findings of this study show that although Merdeka Belajar has had a positive impact, such as increasing student engagement and reducing the administrative burden on teachers, there are still some challenges in its implementation, especially related to the adjustment of learning methods and assessments.